Unheard Voices in Higher Education : Students as Stakeholder - Singh, Ravi S. (National Geographical Journal of India, 2022)
The history of stakeholder concept has completed a century and is still either poorly conceived or entirely ignored in practice, particularly in higher education in India. The studies have proved that stakeholders occupy central position in any organization including (higher) educational institution. Available literature indicates that in most of the developed societies concerns regarding stakeholders, including students, have been at least envisioned; but, this syndrome lacks in developing or under-developed societies and India has been a good example of such syndrome.This article has tried to briefly outline the history of the stakeholder concept in general and higher education in particular. On the basis of the conceptual foundation, it has attempted an analysis of perception of geography students, in higher education, i.e. colleges and universities in India, as stakeholders. The study is primarily based on discussions, interviews and around a quarter century long experiences of the author as geography educator and association with professional academic bodies. The analysis suggests that there is no room for students' voice, in India's higher education system, especially in academic affairs. They are simply receivers and do not have any mechanism to participate in designing and improving the affairs with which they are directly concerned.